Towards Transforming Game Premise: Validating an approach for Developing Cooperative Serious Games - Supara Grudpan; Keattikorn Samarngoon; Jakob Hauge; Jannicke Baalsrud Hauge; Rainer Malaka (Serious Games Society, 2022)
The development of cooperative serious games has specific challenges related to enabling players to achieve both gaming and learning goals in a cooperative fashion. The complexity of gameplay and learning objectives leads to the lack of guidance for the systematic development of cooperative serious games (SGs). To overcome the challenges, we propose a systematic approach to utilize elements of entertainment cooperative games to foster player engagement in SGs called "Transforming Game Premise" to overcome the difficulties. A three-phase guideline is proposed for transforming an existing cooperative entertainment game into a cooperative SG. To demonstrate the application of the proposed guideline, we developed a game prototype that follows the guided steps. We validate the guidelines by conducting two user studies. The first study aims at validating the game's effectiveness for learning purposes of a game developed according to our guidelines. The study showed that the developed game supports players in achieving the defined learning objectives. The second study is a qualitative study evaluating game developers' perception of the usability and usefulness of the Transforming Game Premise guideline. The latter study confirms that the proposed guideline is beneficial for systematically developing SGs. However, it also indicates that the guideline still needs more clarity in identifying the relation between game elements and players' interaction/cooperation.